Proposed Technique of Analysis for Absorber/Transmitter Frequency Selective Surfaces - Eliel P. dos Santos; Antonio L. P. S. Campos; Alfredo Gomes Neto; Maurício W. B. Silva (Journal of Microwaves, Optoelectronics and Electromagnetic Applications, 2021)
Abstract In this paper, we propose a simple technique to analyze absorber/transmitter frequency selective surfaces (FSS). The structure is formed by two FSS, one resistive and one conductive. Both FSS are printed on an FR4 dielectric substrate. The square loop and crossed dipole are the geometries considered in this paper. The technique combines two simple approaches, the equivalent circuit method, and the scattering matrix method. Two prototypes were built for validation purposes. Simulated and measured results are in good agreement.